2022
DOI: 10.1002/cam4.4896
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicines and capecitabine‐based chemotherapy for colorectal cancer treatment: A meta‐analysis

Abstract: This meta‐analysis was conducted to evaluate the efficacy and safety of the addition of Traditional Chinese Medicine (TCMs) to capecitabine‐based regimens for colorectal cancer (CRC) in term of tumor. The eight electronic databases including Cochrane Library, PubMed, Web of Science (WOS), Excerpt Medica Database (Embase), Chinese Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Journals (CQVIP), and Wanfang Database were systematically searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Notably, traditional Chinese medicine has emerged as a promising modality for the treatment of colorectal cancer. 10,11 Salvia miltiorrhiza ranks among the most renowned species within the Salvia genus, which belongs to the Lamiaceae family. 12,13 Salvia miltiorrhiza, first documented in the "Shen-Nong Herbal Classic", is characterized by its bitter taste and slightly cold nature.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, traditional Chinese medicine has emerged as a promising modality for the treatment of colorectal cancer. 10,11 Salvia miltiorrhiza ranks among the most renowned species within the Salvia genus, which belongs to the Lamiaceae family. 12,13 Salvia miltiorrhiza, first documented in the "Shen-Nong Herbal Classic", is characterized by its bitter taste and slightly cold nature.…”
Section: Introductionmentioning
confidence: 99%
“…As an adjuvant therapy for cancer, TCM can mitigate the side effects of chemotherapy, enhance patient immunity, improve patient quality of life, and augment the anti-tumor effect of conventional chemotherapy [ 9 , 10 ]. A meta-analysis demonstrated that associating TCM with capecitabine-based chemotherapy yielded greater anti-cancer efficacy compared to administering capecitabine monotherapy in CRC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous clinical studies have found that TCM combined with chemotherapy in the treatment of CRC may improve clinical symptoms, enhance immunity, and alleviate chemotherapy-induced adverse reactions. 8 - 10 Compound Kushen injection (CKI) is one of the representative and effective Chinese patent medicines, which is extracted from 2 medical herbs: Kushen ( Sophora flavescens Ait.) and Baituling ( Smilax glabra Roxb.).…”
Section: Introductionmentioning
confidence: 99%